Pengaruh Green Accounting, CSR, dan FCF Terhadap Nilai Perusahaan dengan Moderasi Financial Slack - F. Irfando Jovan Kantur; Sigit Puji Winarko; Andy Kurniawan (Yayasan Literasi Ilmiah Indonesia, 2026)
Purpose: This study aims to analyze the effect of green accounting, corporate social responsibility, and free cash flow on firm value with financial slack as a moderating variable in mining companies listed on the Indonesia Stock Exchange for the period 2022–2025. Method: This study uses a quantitative associative causal approach with secondary data from annual reports and sustainability reports. The sample consists of 18 companies selected using purposive sampling with 72 observations. Data analysis was conducted using panel data regression with the Random Effect Model through EViews 12. Finding: Green accounting has a negative and significant effect on firm value, corporate social responsibility has no significant effect, and free cash flow has a positive and significant effect on firm value. Financial slack fails to moderate all three relationships toward firm value. Novelty: This study offers novelty through the integration of green accounting, corporate social responsibility, and free cash flow as determinants of firm value with financial slack as moderator, a combination that has been rarely examined in previous literature, particularly in the mining sector. This study also addresses inconsistencies in prior research by incorporating legitimacy theory, stakeholder theory, and signaling theory within the context of Indonesian mining companies.